Using the Transverse Acetabular Ligament as a Landmark for Acetabular Anteversion: An Intraoperative Measurement. (August 2013) - Inoue, Masahiro; Majima, Tokifumi; Abe, Satomi; Nakamura, Takayuki; Kanno, Taiki; Masuda, Takeshi; Minami, Akio
Purpose: To measure the transverse acetabular ligament (TAL) anteversion in hips with severe deformity, using fluoroscopy–computed tomographic navigation. Methods: 31 hips in 10 men and 19 women aged 40 to 78 (mean, 58.7) years who underwent total hip arthroplasty for primary osteoarthritis (n=6) or osteoarthritis secondary to developmental hip dysplasia (n=19) or congenital hip dislocation (n=6) were included. The severity of hip dislocation was classified according to the Crowe classification; 15 hips were grade 1, 7 were grade 2, 3 were grade 3, and 6 were grade 4. The TAL anteversion was measured using fluoroscopy–computed tomographic navigation. The difference in TAL anteversion between non-dislocated hips (Crowe grade 1, n=15) and dislocated hips (Crowe grades 2–4, n=16) was compared. Results: In all 31 hips, the TAL could be visualised intra-operatively. No patient reported severe pain, early wear, loosening, or dislocation after 2 years. The mean TAL anteversion and inclination angles measured by the navigation system were 26.5° (SD, 8.9°; range, 8°–42°) and 41.5° (SD, 4.6°; range, 32°–49°), respectively. 22 of the 31 hips were in the safe zone. TAL anteversion in non-dislocated and dislocated hips was not significantly different. Inter- and intra-observer mean absolute differences in TAL anteversion were 0.3° and 0.4°, respectively. Conclusion: The TAL is a useful anatomic landmark for total hip arthroplasty in dislocated hips.